Pond fishing in the Congolese cuvette: a story of fishermen, animals, and water spirits - Marion Comptour; Sophie Caillon; Doyle McKey (Revue d'ethnoécologie, 2016)
In the Congo basin, fishing activities are a major source of protein and of income for many households. Fishermen combine a broad range of fishing methods adapted to the seasonality of the floodplain and the particular features of its habitats. Pond fishing is a collective fishing method that consists in emptying pools still flooded during the low-water season in the otherwise dry floodplain in order to capture the fish that have sought shelter there. This practice is widespread in central Africa but has rarely been described in detail. Studies often depict this activity as quite simple and practiced by groups of women only. Our study, conducted in the region of Mossaka, in Congo Republic, reveals another reality. We found that pond fishing engages dozens of men, women and children working together and that this activity is based on a range of skills and know-how. Pond fishing is one of the most productive and socially valued fishing methods in the region. Like the technical dimensions of pond fishing, its social and symbolic dimensions are also little described in literature on the subject. Because pond ownership is a source of income and prestige, pond fishing crystallizes social competition. Yet, the collective nature of this fishery enhances alliances and social networks. Pond fishing is also rooted in beliefs about multiple relationships between humans, fish, crocodiles, and supernatural forces inhabiting the ponds. Pond fishing, like collective fishing as a whole, has been in decline for the last 50 years. Fishermen nowadays engage preferentially in individual techniques. We examine whether these individual fishing methods allow maintenance of the social and cultural functions of inland fisheries.